(3GdJfXje GdUfGYj h EOGQI GdGfJGL (B/s - (3jhfS, YHO GdZahQs ((3GdGScfOQjI(B: s (3GdecJH GdYQHj GdMOjK(B, s, 2010)
(3YQV YGe ddKhQI GdUfGYjI , GdKhQI GdUfGYjI aj GfLdjJQG , UfGYI GdMOjO h GdUdH , GdUfGYGJ GdcjeGhjI h JWhQ GdfTGW GdGfJGLj , eGgjI GdUfGYI h eTGcd GdUfGYI GdeKGdjI, eTGcd JhSjY GdeUfY h JQTjO GdUfGYI , JhWf GdUfGYI GdGfJGLjI , GdeHGfj GdUfGYjI , NWjW GdYGe deHGfj GdeUfY , GdJLgjR GdQCSeGdj efGhdI GdehGO UfGYI GdBdjGJ , GdJfHD HGdGfJGL h OQGSI GdYed h CNjQG GdQbGHI Ydi LhOI GdefJLGJs
Keywords: (3EOGQI GdGfJGLs; (3GdGfJGL GdUfGYjs; (3GdUfGYIs